ANALISIS KRITIS PENDIDIKAN AKHLAK BAGI PESERTA DIDIK (Bangun Rancang Pemikiran Hamka) - Khoirotu Alkahfi Qurun (Al Wildan: Jurnal Manajemen Pendidikan Islam, 2022)
This article discusses a critical analysis of moral education for students (Prof. Dr.Hamka thinking design). Education today is experiencing a lot of moral decadence and a loss of social values which are marked by promiscuity, drinking, brawls, drugs, and many more things that come out of morality. This is part of deviant behavior among adolescents, youth and society. Furthermore, Hamka, an Indonesian scientist and intellectual figure, Prof. Dr. Hamka. As it is understood that character plays a very important role in shaping a person's attitude and behavior, both as an individual, society and nation, in order to achieve life goals in accordance with the right guidance. Character development becomes urgent, in the midst of developing attitudes and behaviors that conflict with values (norms), both religious and cultural values (norms). This research is library research (Library Research) where the data is obtained from reading and collecting books related to research, such as primary data and secondary data. After getting the data, then the data is processed using the reading method at the symbolic stage, namely reading that is not carried out thoroughly but captures the contents of the data, reading at the semantic level, namely reading in detail, decomposing, and capturing the essence of the data. Then these data were analyzed using the Verstehen, Holistic, and Interpretation methods. Character development based on monotheism values, both textually sourced from the Qur'an and al-Hadith as well as originating from the thoughts of Islamic scientists, such as Hamka reconstructing these thoughts and concepts aims to prepare humans, especially new Muslim scientists who always have an Islamic commitment, as guidelines for the right management of life